Labour hoarding during the pandemic: Assessing the impact of job retention schemes in Europe - Ebbinghaus, B; Lehner, L (EUROPP – European Politics and Policy, London School of Economics and Political Science, 2021)
Job retention schemes have helped Europe to avoid mass unemployment during the Covid-19 pandemic. Bernhard Ebbinghaus and Lukas Lehner write that while these schemes had an immediate impact during lockdown, the future development and long-term consequences of job retention policies remain uncertain.